2008
DOI: 10.1002/tox.20414
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methyl parathion exposure on development and reproduction in the viviparous fish Girardinichthys multiradiatus

Abstract: Methyl parathion (MeP), an insecticide commonly used in Mexico, has been detected in water bodies adjacent to agricultural crops and is accumulated in the tissue of the amarillo (Girardinichthys multiradiatus), a viviparous fish unique to Central Mexico. Evidence of MeP accumulation in a G. multiradiatus population prompted assessment of the consequences of exposure to MeP during the gestation period and adult life. We exposed adult fish to MeP in the diet at concentrations ranging from 0.001 to 0.165 microg/g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Fish were measured (mm) and weighed (g) at the beginning and at the end of the experiment, and growth was calculated as the percentage of initial body length ([final length-initial length/initial length] x 100). As reported originally (ArellanoAguilar & Macías Garcia, 2009) the accumulation of MeP in adult G. multiradiatus follows a dose-dependent relationship. Fish exposed to concentrations of 0.008, 0.02 and 0.04 μg of MeP for 30 days showed a reduction in size and weight.…”
Section: What Are the Effects Of Early Sub-lethal Exposure Of Mep In supporting
confidence: 76%
See 2 more Smart Citations
“…Fish were measured (mm) and weighed (g) at the beginning and at the end of the experiment, and growth was calculated as the percentage of initial body length ([final length-initial length/initial length] x 100). As reported originally (ArellanoAguilar & Macías Garcia, 2009) the accumulation of MeP in adult G. multiradiatus follows a dose-dependent relationship. Fish exposed to concentrations of 0.008, 0.02 and 0.04 μg of MeP for 30 days showed a reduction in size and weight.…”
Section: What Are the Effects Of Early Sub-lethal Exposure Of Mep In supporting
confidence: 76%
“…One obvious way in which behaviour is influenced by pesticides is through their teratological effects during embryogenesis. For instance, malformations produced by sublethal exposure to OP during embryonic development also cause deficient swimming (Bonfanti et al, 2004;Arellano-Aguilar & Macías Garcia, 2009). Pesticides can also have direct adverse effects on swimming behaviour when these interact with AChE activity, as is the case of OPs, or when they interfere with other and physiological processes (see Jones & Reynolds, 1997).…”
Section: Sub-lethal Exposure Of Ops and Intersexual Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, honey bees could adsorb microencapsulated MP during foraging and carry it back to the hive, leading to a sustained slow release of the pesticide, resulting in high MP residues (4.8 mg kg −1 ) and mortality [ 12 ]. In addition, MP exposure resulted in significant reductions in body weight and growth rate, as well as an increased risk of deformity in Amarillo fish [ 13 ]. Furthermore, MP exposure was found to be genotoxic in rats, causing necrotic edema of kidney tissue and leading to severe malformations of the reproductive system [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Methyl parathion is metabolized by both plants and animals and it is not expected to persist or bioconcentrate. However, studies have reported that Girardinichthys multiradiatus captured in the Ignacio Ramirez Dam (Mexico) accumulated methyl parathion more than 13,000 times in relation to water levels of this compound [ 6 , 7 ]. Methyl parathion can be detoxified by dealkylation by glutathione S-transferases (GST) [ 8 ], whereas methyl paraoxon can be removed from blood by scavenger enzymes, such as carboxylesterase and cholinesterases, or degraded by paraoxonase, yielding 4-nitrophenol and dimethylphosphoric acid [ 9 ].…”
Section: Introductionmentioning
confidence: 99%